Fecundity of Wild Northern Bobwhite Hens Under Hatchery Conditions - John T. Baccus; Kevin W. Dees; Michael F. Small; Thomas R. Simpson (National Quail Symposium Proceedings, 2017)
We describe egg production by 88 pairs of randomly selected, mature, wild-caught northern bobwhite (Colinus virginianus) hens housed under optimal conditions of food, water, climate, and a 17-hr photoperiod in a hatchery. We collected eggs daily using an 18-day period to differentiate between clutches. Hens continuously laid eggs until ceasing production. We evaluated number of eggs laid by each hen individually and hens collectively including total number, number/clutch, number/day, hatching success, and egg mass. Eighty-six hens produced 5,888 eggs. Number of eggs produced by individual hens ranged from 0 to 172 over 200 days. Mean number of eggs laid/hen/day was 0.86. Clutch size ranged from 0 (n 1⁄4 2) to 12 (n 1⁄4 1). Mean number of eggs/clutch was 8.57. There was a strong correlation between clutch size and number of clutches. Some hens demonstrated continuous production of several large clutches. Hatching success of 5,793 eggs included for analysis was 61.6% (3,571 hatched, 2,222 failed to hatch). Hatched eggs had a greater mean mass compared to those that did not hatch.
Keywords: Colinus virginianus; differential production; hatchery; northern bobwhite; reproduction; Texas